Traumatic injuries to the pancreas: analysis of 17 cases - Cassinelli, Daniel (Cirugía del Uruguay, 1974)
This report comprises a series of 17 cases of pancreatic traumatism, but excludes those of surgical origin. The author revises existing bibliography on the subject and refers to its increasing frequency, the difficulty in diagnosing such cases, their severity and the various surgical procedures and their results.